KARAKTERISTIK FISIKOKIMIA DAN MIKROBIOLOGIS MINUMAN FERMENTASI KOMBUCHA KUNIR PUTIH (Curcuma mangga Val.) SEBAGAI PANGAN FUNGSIONAL - Saputro, Asepto Edi; Laswati, Dyah Titin; Puspitasari, Diah (Jurusan Ilmu dan Teknologi Pangan Universitas Halu Oleo, 2025)
Kombucha is a tea-based fermented drink that contains various bioactive compounds that are beneficial to health. The innovation was carried out by adding white turmeric (Curcuma mangga Val.), which is rich in antioxidants from curcuminoid compounds. This study aimed to evaluate the physical characteristics (thickness and weight of SCOBY), chemical (pH, Antioxidant Activity, Acetic Acid, Alcohol) and microbiological (AAB and yeast). This study used a Non-Factorial Complete Random Design, with 1% tea treatment, 0.5% Tea + 0.5% White Turmeric and 1% White Turmeric. The results of this study showed that kombucha that had been fermented for 14 days with the highest concentration of white turmeric addition of 1% had a SCOBY thickness and weight of 2.23 mm and 35.58 g, respectively. The IC50 value in the treatment of 1% white turmeric kombucha was 290.40 μg/mL. The 1% white turmeric kombucha also has a pH value of 3.5, acetic acid 0.29%, and 0.21% alcohol that has met standards based on Kombucha Brewers International. In addition, 1% white turmeric kombucha has AAB of log 3.69 CFU/ml and log 3.63 CFU/ml of yeast. This research still has the potential to be further developed, especially kombucha drinks as functional foods.